Endo-sponge Assisted Early Surgical Closure of Ileal Pouch-anal Anastomotic Leakage Preserves Long-term Function: A Cohort Study. (4th May 2019) - Wasmann, Karin A; Reijntjes, Maud A; Stellingwerf, Merel E; Ponsioen, Cyriel Y; Buskens, Christianne J; Hompes, Roel; Tanis, Pieter J; Bemelman, Willem A
Abstract: Background and Aims: Endo-sponge [Braun Medical] assisted early surgical closure [ESC] is an effective treatment to control pelvic sepsis after ileal pouch-anal anastomosis [IPAA] leakage, and became standard treatment in our centre from 2010 onwards. The aim of this cohort study was to assess the long-term pouch function of ulcerative colitis [UC] patients treated with ESC or conventional management [CM] for anastomotic leakage after IPAA. Methods: Consecutive patients who underwent an IPAA for UC between 2002 and 2017 were included. Patients treated with ESC [2010–2017] or CM [2002–2009] for anastomotic leakage were compared with control patients without anastomotic leakage of the corresponding time period. Main endpoints were long-term pouch function on a 3-point scale and pouch failure, as measured with the validated pouch dysfunction score questionnaire. Results: Some 280 of 334 patients [84%] returned the pouch dysfunction questionnaire, of whom 18 were treated with ESC and 22 with CM for anastomotic leakage. Control cohorts included 133 [2010–2017] and 107 patients [2002–2009]. Between ESC-treated patients and control patients, pouch function [ p = 0.647] and pouch failure rates [0/18 versus 5/133, p > 0.99] were similar. CM resulted in worse pouch function [ p = 0.016] and a higher pouch failure rate [5/22 versus 5/107, p = 0.013] compared with control patients. Conclusions: ESC, in contrast to CM, for IPAA leakage in UC patients is associated with preservation of pouch function and preclusion of pouch failure, probably due to early and effective treatment of pelvic sepsis.